Preparation Of Activated Carbon From Pineapple Peel And Pomelo Peel For Dyes Removal: Equilibrium, Kinetic And Thermodynamic Studies - Rosli, Nur Aisyah (2012)
The production of activated carbon from pineapple peel (PiPAC) and pomelo peel (PoPAC) through physiochemical activation consisting of potassium hydroxide (KOH) impregnation and carbon dioxide (C02) gasification has been successfully investigated. Activated carbon produced were used for removal of methylene blue (MB), methyl red (MR) and remazol brilliant violet 5R (RBV) dyes from aqueous solution. The experimental design results revealed that the activation temperature, activation time and KOH impregnation ratio (IR) were significant factors influencing adsorption performance for MB, MR and RBV. The optimum preparation conditions of PiPAC and PoPAC for MB removal were at activation temperature, activation time and IR of 732°C, 1.96 hour, 3.00, and 750°C, 2.19 hour, 2.12, respectively. Whereas optimum preparation conditions obtained for PiPAC and PoPAC for MR removal were at activation temperature, activation time and IR of 748°C, 2.13 hour, 3.00, and 800°C, 2.19 hour, 2.96, respectively.